Species interactions and climate change: How the disruption of species co‐occurrence will impact on an avian forest guild. (10th January 2020) - Brambilla, Mattia; Scridel, Davide; Bazzi, Gaia; Ilahiane, Luca; Iemma, Aaron; Pedrini, Paolo; Bassi, Enrico; Bionda, Radames; Marchesi, Luigi; Genero, Fulvio; Teufelbauer, Norbert; Probst, Remo; et al.
Abstract: Interspecific interactions are crucial in determining species occurrence and community assembly. Understanding these interactions is thus essential for correctly predicting species' responses to climate change. We focussed on an avian forest guild of four hole‐nesting species with differing sensitivities to climate that show a range of well‐understood reciprocal interactions, including facilitation, competition and predation. We modelled the potential distributions of black woodpecker and boreal, tawny and Ural owl, and tested whether the spatial patterns of the more widespread species (excluding Ural owl) were shaped by interspecific interactions. We then modelled the potential future distributions of all four species, evaluating how the predicted changes will alter the overlap between the species' ranges, and hence the spatial outcomes of interactions. Forest cover/type and climate were important determinants of habitat suitability for all species. Field data analysed with N‐mixture models revealed effects of interspecific interactions on current species abundance, especially in boreal owl (positive effects of black woodpecker, negative effects of tawny owl). Climate change will impact the assemblage both at species and guild levels, as the potential area of range overlap, relevant for species interactions, will change in both proportion and extent in the future. Boreal owl, the most climate‐sensitive species in the guild, will retreat, and the range overlap with its main predator, tawny owl, will increase in the remaining suitable area: climate change will thus impact on boreal owl both directly and indirectly. Climate change will cause the geographical alteration or disruption of species interaction networks, with different consequences for the species belonging to the guild and a likely spatial increase of competition and/or intraguild predation. Our work shows significant interactions and important potential changes in the overlap of areas suitable for the interacting species, which reinforce the importance of including relevant biotic interactions in predictive climate change models for increasing forecast accuracy. Abstract : Interspecific interactions are crucial in determining species occurrence and community assembly. This study analysed the distributions of four species, which are affected by reciprocal interactions and will be impacted by climate change. The latter will impact the assemblage both at species and guild levels, as the potential area of range overlap, relevant for species interactions, will change in both proportion and extent in the future, causing the geographical alteration or disruption of species interaction networks. Relevant biotic interactions should be included in predictive climate change models for increasing forecast accuracy.